Optimizing the potential of the river through the “merti kali” program to support the sustainable communities - Endah Saptutyningsih; Berli Paripurna Kamiel; Dimas Putro Nugroho; Ferry Armansyah (Journal of Community Service and Empowerment, 2023)
The development of digital technology and virtual reality has also given birth to virtual tourism innovations that have an impact on increasing the community's economy through training. This program is carried out to create virtual tourist villages, especially based on virtual tourism batik, so that batik craftsmen have more time to promote their products and the tourist aspect. The virtual tour-based batik village aims to empower the batik artisan community to be more active in utilizing digital application platforms to market their products and produce practical applications for marketing. This digital application makes it easier for buyers to find out the promotions being carried out by Bekasi batik by utilizing gadgets and taking advantage of the digital world. The training method uses a case study approach, discussion, lecture, and ends with a training evaluation. The results of the study are based on the evaluation results of the user experience of batik craftsmen in the city of Bekasi, out of 50 respondents it is found that 55% strongly agree that training materials and virtual tour systems that are socialized are easy to access, can develop digital villages based on web virtual tours and as a forum for batik promotion Bekasi city. In the aspect of achieving the goals of the Bekasi city batik craftsmen participants, out of 50 respondents the result was that 65% strongly agreed that the learning objectives of the training and virtual tour system met the expectations of the respondents. It is the hope of the training participants that the problem of marketing the virtual tour system will be a solution to expand the marketing of batik in the City of Bekasi.